2017
DOI: 10.1371/journal.pone.0183426
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves alcoholic fatty liver disease by downregulating HIF-1α expression and mitochondrial ROS production

Abstract: Oxidative stress has been demonstrated to be involved in the etiology of alcoholic fatty liver disease (AFLD). Previous studies had demonstrated that resveratrol (RES) could reduce oxidative stress by different mechanisms. However, the effect of RES on alcohol-induced fatty liver remains unclear. In the present study, a total of 48 male SD rats were divided into three groups: Control, AFLD, and RES groups. Rats were administered with either nothing or 65% vol/vol alcohol (5 ml/kg/day in the first three days, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…Furthermore we also observed increased mitochondrial ROS and serum nitrite/nitrate in steatosis and NASH animals. Recently Ma et al () also reported the similar findings in high fat diet fed animals.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore we also observed increased mitochondrial ROS and serum nitrite/nitrate in steatosis and NASH animals. Recently Ma et al () also reported the similar findings in high fat diet fed animals.…”
Section: Discussionsupporting
confidence: 60%
“…ROS are generated during metabolic process of the cells, if it is unchecked by antioxidant defense system, cell will incline toward oxidative stress (Alcala et al, 2017;Lubos, Loscalzo, & Hand, 2011;Mortezaee & Khanlarkhani, 2017). In few conditions ROS could react with nitric oxide and generate higher reactive nitrogen species (RNS) known as peroxy nitrite (Chance, Sies, & Boveris, 1979;Hansen et al, 2016;Liochev & Fridovich, 2007 Recently Ma et al (2017) also reported the similar findings in high fat diet fed animals.…”
Section: Discussionmentioning
confidence: 73%
“…Resveratrol also improved high-fat diet (HFD)-induced fatty liver by downregulating adipose differentiation-related proteins and increasing the numbers of CD68 + Kupffer cells [9]. As for chemical-induced liver diseases, resveratrol could markedly restore the morphology and function of alcohol-injured liver through inducing autophagy, or downregulating hypoxia-inducible factor 1α (HIF-1α) expression [85,86]. In addition, resveratrol ameliorated CCl 4 -induced liver injury by blocking the Notch signaling pathway [82].…”
Section: Liver Diseasesmentioning
confidence: 99%
“…In vivo Mice 0.2% of diet Improving HFD-induced fatty liver by downregulating adipose differentiation-related proteins and increasing the numbers of CD68 + Kupffer cells [9] In vivo Rats 10 mg/kg Attenuating hepatic fibrosis by restoring the architecture and normalizing collagen deposition, mainly due to its antioxidative activities and downregulation of α-SMA [80] In vivo Rats 50, 100 mg/kg Alleviating NAFLD by upregulating LDLR and SRB1 gene expressions [83] In vivo Rats 250 mg/kg/day Downregulating HIF-1α expression and mitochondrial ROS production [85] In vitro; In vivo HepG2 cells; Mice 45 µmol 10, 30, 100 mg/kg Restoring the morphology and function of alcohol-injured liver through inducing autophagy [86] In vivo Rats 10 mg/kg Mitigating liver cirrhosis by improving the homing of bone marrow-derived mesenchymal stem cells [87] Diabetes…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Hypoxia‐inducible factor‐1α (HIF‐1α) is an important determinant of lipid accumulation and alcoholic steatosis pathogenesis (Nath et al, ). Resveratrol was also reported to improve lipid accumulation in alcoholic liver injury by downregulating expression of HIF‐1α (Ma et al, ).…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%